2015
DOI: 10.1007/s10683-015-9469-5
|View full text |Cite
|
Sign up to set email alerts
|

Procedural fairness in lotteries assigning initial roles in a dynamic setting

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…There is extensive evidence that individuals care not only about the nature of the final distribution of income but also about the procedures that brought it about (e.g. Rabin, 1993;Hoffman et al, 1994;Konow, 1996Konow, , 2000Frey et al, 2004;Bolton et al, 2005;Almås et al, 2010;Dal Bó et al, 2010;Jakiela, 2011;Grimalda et al, 2016). There are numerous theoretical and empirical studies of meritocracy in the behavioral economic tradition, with a number of theoretical conceptions of merit-based equity having been put forth, often combined with experimental tests.…”
Section: Related Literaturementioning
confidence: 99%
“…There is extensive evidence that individuals care not only about the nature of the final distribution of income but also about the procedures that brought it about (e.g. Rabin, 1993;Hoffman et al, 1994;Konow, 1996Konow, , 2000Frey et al, 2004;Bolton et al, 2005;Almås et al, 2010;Dal Bó et al, 2010;Jakiela, 2011;Grimalda et al, 2016). There are numerous theoretical and empirical studies of meritocracy in the behavioral economic tradition, with a number of theoretical conceptions of merit-based equity having been put forth, often combined with experimental tests.…”
Section: Related Literaturementioning
confidence: 99%
“…Several experimental studies have shown that the procedure accountable for a payment distribution affects subjects' redistribution decisions reflecting fairness perceptions of the applied procedures (e.g., Akbaş, Ariely, and Yuksel 2019; Blount 1995; Bolton, Brandts, and Ockenfels 2005; Cappelen et al 2007, 2013; Konow 2000). When institutions violate procedural‐fairness norms, people may refuse to accept unequal outcomes (Grimalda, Kar, and Proto 2016), may engage in cheating (Gill, Prowse, and Vlassopoulos 2013), lying (Banerjee, Gupta, and Villeval 2018), sabotage (Ambrose, Seabright, and Schminke 2002; Fehr 2018), or theft (Greenberg 1990) in retribution. Moreover, procedural unfairness at the workplace can lower workers' intrinsic motivation (e.g., Breza, Kaur, and Shamdasani 2018; Cohn et al 2014; Gächter and Thöni 2010; Heinz et al Forthcoming), work satisfaction (Breza, Kaur, and Shamdasani 2018), and labor supply (Bracha, Gneezy, and Loewenstein 2015).…”
Section: Introductionmentioning
confidence: 99%
“…one that results from unfair chances (e.g., Bolton et al, 2005;Grimalda et al, 2016). In stark contrast, we find that behavior of workers is insensitive to initial chances when they are generated by an unspecified source, as labor supply is almost identical under the payment schemes UNEQFAIR and UNEQUNFAIR.…”
Section: Viib Fairness Of Chancesmentioning
confidence: 65%